1998
DOI: 10.1177/019262339802600307
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin Expression Patterns in the Rat Respiratory Tract as Markers of Epithelial Differentiation in Inhalation Toxicology. I. Determination of Normal Cytokeratin Expression Patterns in Nose, Larynx, Trachea, and Lung

Abstract: Cytokeratin (CK) polypeptides constitute the intermediate filament cytoskeleton of epithelial cells. The patterns of CK expression can be regarded as specific markers for the epithelial differentiation status. Our objective was to map the cell type-specific CK expression patterns at all representative sites of the respiratory tract of untreated rats to use as a base for the detection of inhalation exposure-related differentiation changes. Using routine paraffin-embedded sections and a panel of well-characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…Details of the procedures and the defined section levels are given elsewhere (26). Tissues were removed and fixed in formaldehyde-containing fixatives: nasal cavity in neutral buffered formalin solution followed by decalcification in nitric acid, and lungs with larynx and trachea in ethanolhcetic acid/formaldehyde/saline (15).…”
Section: Necropsy and Routine Histopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the procedures and the defined section levels are given elsewhere (26). Tissues were removed and fixed in formaldehyde-containing fixatives: nasal cavity in neutral buffered formalin solution followed by decalcification in nitric acid, and lungs with larynx and trachea in ethanolhcetic acid/formaldehyde/saline (15).…”
Section: Necropsy and Routine Histopathologymentioning
confidence: 99%
“…Details of the immunostaining procedure and the individual scoring are given elsewhere (26). Paraffin-embedded sections were dewaxed and immunostained following antigen retrieval by protease or microwave treatment using an antibody panel with defined specificity for rat CK (27) (Table 11).…”
Section: Bn~~iii~iolii~tological Procedures and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…No altered cell morphology and cytoskeletal organization was observed. It is well documented that cytokeratin polypeptides constitute the intermediate filament cytoskeleton of epithelial cells (38). Further, the patterns of cytokeratin expression represent markers of epithelial differentiation status.…”
Section: Discussionmentioning
confidence: 99%
“…We found that SILECC had an abundant level of cytokeratin suggesting that this normal lung cell culture is of epithelial origin. Abundant staining of cytokeratin found in SILECC using pan-Cytokeratin antibody can also be attributed to the fact that normal lung tissue has been known to harbor expression of various forms of cytokeratin polypeptides (38).…”
Section: Discussionmentioning
confidence: 99%